Analysis of Rooftop Solar Power Plant Planning for Lecturers' Houses and Solar Street Lighting at Campus 4 Unkhair Sofifi - Idham A Djufri; Faris Syamsudin (International Journal Of Electrical Engineering and Inteligent Computing, 2025)
The utilization of solar energy as a substitute for fossil energy has become a necessity in facing the global energy crisis due to the increasingly critical dependence on fossil energy. Additionally, the use of fossil energy causes environmental damage/climate crisis. The utilization of solar energy not only alleviates the global energy crisis but also produces environmentally friendly energy that can reduce carbon emissions resulting from the combustion of fossil fuels. Currently, the use of solar energy is not only implemented in areas that are not yet served by PLN electricity, but it is also used in almost all public facilities with the aim of transitioning energy from conventional electricity to renewable electricity. One of the uses of solar energy is through a centralized system to meet the electricity needs in the surrounding area, reducing the use of electricity sourced from fossil fuels, and decreasing carbon emissions that cause climate damage. This research aims to utilize solar energy to reduce the use of fossil fuel-based energy, which can harm the climate and environment, as well as to calculate the investment costs of using centralized solar power plants (PLTS). The method used in this research is data collection and the calculation of technical and economic needs. The research results indicate that the rooftop solar power system for the lecturer's house has a total power of 7,920 Watts, using 4 solar modules with a capacity of 450 wp per module. The battery capacity used is 120 Ah 48 volts, with 4 units. For solar street lighting, a total of 17 solar streetlight poles were obtained, each 7 meters high, with a lamp power of 40 watts per pole. The solar module capacity is 100 Wp and the battery capacity is 100 Ah.